O feminino mágico em Temporada de furacões, de Fernanda Melchor - Hübner, Rafaela Emmanuelli (2025)
This paper investigates the symbolic figure of the witch as an expression of archetypes of the collective unconscious, based on the Analytical Psychology of Carl Gustav Jung and the contributions of Clarissa Pinkola Estés, Eliade and Campbell. The general objective of this research is to analyze the character known as the Witch, from the novel Hurricane Season by Fernanda Melchor, focusing on her symbolic and narrative construction through the lens of contemporary feminist criticism, and exploring how her portrayal reflects social mechanisms of exclusion and oppression of women in Latin American society, raising the problem of how the character of the Witch is constructed, both symbolically and narratively, in the novel Hurricane Season, and how this construction reflects social discourses on marginalized femininity in contemporary Latin American literature. The study discusses how the archetypes of the Shadow, the Great Mother and the Wild Woman manifest themselves in the construction of the image of the witch, highlighting her function as a representation of repressed, ambivalent and instinctive aspects of the feminine in the individual and collective psyche. It analyzes how the witch embodies dark contents, socially projected onto women who escape the patterns of behavior established by patriarchal culture, using Silvia Federici. It performs a reading of the literary work Hurricane Season, by the Mexican author Fernanda Melchor, highlighting the way in which the narrative portrays marginalized and stigmatized female characters, whose social imaginary refers to the archetypes analyzed. The Witch of Matosa, the central character of the plot, emerges as a symbol of the woman-witch, victim of exclusion, violence and gender prejudice, reflecting the collective fear of female otherness. It is argued that the redefinition of the witch, as an archetypal symbol, enables a critical reading of the social constructions of gender, the marginalization of the feminine and the forms of symbolic violence that persist in narratives and in the contemporary imagination.